Disemination model of health information for rural poor citizen in dongko trenggalek - Diah Handayani (IAIN Salatiga, 2020)
This study aims to describe the dissemination model developed in Dongko District, Trenggalek Regency. This study uses a dissemination model approach by S. Notoadmodjo which divides the elements of communication into four parts, namely health communicators, media messages, effects and communication context. The data collection process was obtained from observations in rural areas in Dongko Village in Trenggalek Regency. Interviews were conducted with several health personnel such as village midwives, village nurses, posyandu volunteers and PMD (Village Community Empowerment) officers. The results showed that health dissemination for the rural poor in Dongko District was limited to the dissemination of health information and the distribution of health assistance for the rural poor. The role of education through literacy in health media in rural areas is dominated by the role of village leadership and the lack of public awareness of changing their health behavior. This is because changes in behavior through daily communication to educate the public have not been carried out optimally either through personal communication or group communication in rural areas.